Building capability for in situ quantitative characterisation of the ocean water column using acoustic multibeam backscatter data. Catalyst: Seeding Activity Report - Lamarche, G; Lucieer, VL (University of Tasmania, 2018)
The objective of this project was to enhance our ability to develop protocols and methodologies foridentifying and quantifying features such as gas, oil, and freshwater in the ocean using marine acoustictechnology. Such approaches are still in their infancy but since New Zealand has sovereign rights over4,000,000 km 2 of ocean in which resources (fish, minerals, hydrocarbons) are vast but mostlyunquantified, they potentially provide considerable economic, environmental and cultural benefits toNew Zealand by improving our capacity to manage our marine estate. This project has established amultidisciplinary research consortium of internationally recognised experts in marine acoustics andgeophysics, spatial analysis and environment, from New Zealand (NIWA, University of Auckland), France(CNRS-Gosciences Rennes, IFREMER), Australia (Institute for Marine and Antarctic Studies, Universityof Tasmania, Hobart, Tasmania - IMAS-UTAS), USA (University of New Hampshire, Centre for Coastal andOcean Mapping - UNH-CCOM), Germany (GEOMAR), and Belgium (FPS Economy). During the April 2017workshop, in Rennes, France, we reviewed the state of scientific and technological knowledge on water columndata, identified key technical issues (data acquisition, use and transfer), and designed theconcept of an ambitious marine geophysical survey in New Zealand required to address the keyscientific questions. During year two, we finalised an ambitious multi-institute survey proposal. Theproject culminated in a New Zealand funded 20-day voyage of R.V. Tangaroa to which twentyparticipants from 8 organisations brought specific expertise and equipment. The acoustic surveyfocused on a large active hydrothermal vent field in the Bay of Plenty and resulted in the collection of anoutstanding marine acoustic and ground truthing dataset over intensive methane and CO 2 vents. Oursurvey proved exceptionally successful and demonstrated the potential to differentiate methane andCO 2 bubbles in the water column. A result thought impossible up until now. The research will lead tomultiple collaborative publication